(untitled) (Physical Education, Health and Social Sciences, 2025)
Stalking is a growing social and psychological issue, which involves the constant and unwanted behavior of certain people with a tendency to result into fear, stress, and significant psychological damage. The current research studies stalking with a social-psychological perspective and the focus is made on the negative outcomes that are imposed by victims. The conceptualization of criminal harassment is a deviant behavior that is regulated to adhere to existing social norms, power structure, and individual psychological characteristics of the person. This study used a quantitative research design to explain the relationship between stalking and its psychological implications. The data collection involved the usage of a structured questionnaire that included a Likert-type scale that was aimed at registering both an individual experience of stalking and the aftermath of such experience in terms of its impact on the mental health and the social functioning of victims. The Statistical Package of the Social Sciences ( SPSS) was used to carry out the statistical analysis using both the descriptive and inferential methods to reveal the patterns and relationships. The results indicated that stalking has a huge negative effect on the psychological health of the victims, which includes anxiety, fear, psychological distress, sleep disturbance, and social isolation. The paper also highlights the importance of social-psychological factors e.g. the societal acceptance of bullying and decline in informal social control in perpetuating the acts of bullying. These findings shed light on the necessity to consider stalking as a serious psychosocial and mental health problem that has implications in the support of the victim, community education, and preventive measures. Pearson correlation, as a form of inferential analyses, was applied in order to test the association between stalking and psychological impacts that were experienced by victims.